AYAT-AYAT KEBEBASAN BERAGAMA DALAM PERSPEKTIF NASAKH: KAJIAN TERHADAP PENAFSIRAN IBN KATHÃR DAN RASHÃD RIDÃ - Hasan, Moh Abdul Kholiq (Mutawatir : Jurnal Keilmuan Tafsir Hadith, 2016)
This article aims to find out how the opinion of IbnKathÃ®r and RashÃ®d Rid}a about naskh in the Qurâan? How did IbnKathÃ®r and RashÃ®d Rid}a interpret the verses about religious freedom that were claimed to be annulled? And what are the implications for the interpretation of texts about religious freedom? The research method is a library research, with the object of religious freedom verses claimed to be annulled in the book of IbnKathÃ®r and RashÃ®dRid}Ã¢. Using the descriptive-analytical and comparative analysis with Hermeneutics Romansis Friedrich Daniel Ernst Schleiermacher approach, the article argues thatIbnKathÃ®r acknowledges the existence of naskh in the Qurâan, but not everything said as annulled is received by him. While RashÃ®d Rid}a rejects the theory of naskh in the Qurâan. Related to interpretation, IbnKathÃ®r and RashÃ®d Rid}a reject the opinion of naskh against the verses of religious freedom. Though RashÃ®d Rid}a seems more emphatically for his refusal. Being the most important implications are that the verses of religious freedom are fundamental and universal, so it is impossible for them to be annulled; the need for change in the paradigm of the law lapsed; and the creation of a peaceful religious life.